Simulation of forces in the supports of machines of the main technological purpose on the example of a fully mobile crane - Sladkova L.A.; Grigorev P.A.; Krylov V.V. (Научно-технический вестник Брянского государственного университета)
When working fully mobile crane on week soil due to drawdown of the outriggers, the possible misalignment of the frame with located on it a turntable with lifting equipment. This disrupts the operation of the crane, leads to loss of stability and disruption of its safe operation. Usually used to ensure the levelling under the chassis of the crane, outriggers (outriggers). It is also possible to use automated systems to ensure the stability of crane equipment, but they do not always provide the proper level of safety. The design of the device of ensuring stability working at the expense of increase in the area of a basic surface of the crane is offered. Considering a self-propelled crane (vehicle) as a connected system with an inertial reference system located in its center of gravity at an arbitrary time, the physical nature of the uneven pressure distribution under the supports of the running equipment at the initial installation of the crane was revealed. On the basis of the obtained theoretical dependences the variant of modernization of the fully mobile crane is offered. The practical implementation of the upgraded design will improve the stability of the crane when working on week soils and provide a high level of safety due to the reduction of specific pressure on the ground.